THE The Implementation of Text-Based Teaching to Enhance Students' Reading Skills at Senior High School (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to evaluate the effectiveness of Text-Based Teaching (TBT) in improving the reading skills of recount texts of grade XI students at SMK TP 45. The study used a quantitative approach with a quasi-experimental design with a post-test only control group type. The study population consisted of all grade XI students of SMK TP 45, with a sample of two classes selected using a purposive sampling technique, namely one class as the experimental group and one class as the control group. Research data were collected through a multiple-choice reading test of 25 items that had passed validity and reliability tests, as well as structured interviews to obtain supporting information about the learning process. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, and independent samples t-tests. The results showed that students who received learning using the Text-Based Teaching method had better reading skills in recount texts than students who followed conventional learning. These findings indicate that the Text-Based Teaching method is effective in improving students' understanding of text structure, linguistic elements, and content of recount texts. Thus, this method can be used as an alternative learning method to improve students' reading skills at vocational high school level.